2020
DOI: 10.1080/20013078.2020.1753420
|View full text |Cite
|
Sign up to set email alerts
|

DC‐SIGN mediated internalisation of glycosylated extracellular vesicles from Schistosoma mansoni increases activation of monocyte‐derived dendritic cells

Abstract: Helminths like Schistosoma mansoni release excretory/secretory (E/S) products that modulate host immunity to enable infection. Extracellular vesicles (EVs) are among these E/S products, yet molecular mechanisms and functionality of S. mansoni EV interaction with host immune cells is unknown. Here we demonstrate that EVs released by S. mansoni schistosomula are internalised by human monocyte-derived dendritic cells (moDCs). Importantly, we show that this uptake was mainly mediated via DC-SIGN (CD209). Blocking … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
55
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 77 publications
7
55
0
1
Order By: Relevance
“…Additionally, the monosaccharide fucose can be highly immunogenic and many antibodies in the human host are directed against fucose containing glycan motifs 12 . Fucose-containing glycan motifs, such as LeX and LDN-F, interact with innate immune cells via C-type lectin receptors and can influence the outcome of immunological responses 13 17 . For instance, the Th2 inducing capacity of the S. mansoni soluble egg antigen omega-1 is glycosylation dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the monosaccharide fucose can be highly immunogenic and many antibodies in the human host are directed against fucose containing glycan motifs 12 . Fucose-containing glycan motifs, such as LeX and LDN-F, interact with innate immune cells via C-type lectin receptors and can influence the outcome of immunological responses 13 17 . For instance, the Th2 inducing capacity of the S. mansoni soluble egg antigen omega-1 is glycosylation dependent.…”
Section: Introductionmentioning
confidence: 99%
“…The specificity is probably imposed by membrane associated proteins or other cell surface molecules. It was shown that the uptake of the S. mansoni schistosomula-derived EVs by monocyte-derived DCs is mainly mediated via the C-type lectin receptor DC-SIGN (CD209) (Kuipers et al, 2020). DC-SIGN is an adhesion molecule that recognizes and binds highmannose-containing glycoproteins on pathogens, and is present on the surface of both macrophages and dendritic cells.…”
Section: Schistosomal Ev-guidancementioning
confidence: 99%
“…EVs are cell-derived membrane-enclosed particles that varied by their size, content, and intra-cellular origin. It was demonstrated that both S. japonicum and S. mansoni adult worms, as well as S. mansoni schistosomula and S. japonicum eggs, secrete EVs ( Wang et al., 2004 ; Nowacki et al., 2015 ; Sotillo et al., 2016 ; Zhu et al., 2016a ; Zhu et al., 2016b ; Samoil et al., 2018 ; Kuipers et al., 2020 ; Meningher et al., 2020 ). This review is focused on the current knowledge on the way by which schistosomal EVs modulate the immune response, mostly as was learned from the murine model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Determining whether they are potential vaccine antigens could help achieve schistosomiasis control. Efforts have also been made to understand how these schistosome-specific proteins are packaged within exosomes and further delivered and taken up by host cells ( 58 ). This work could provide new insights into the strategies of competently targeting exosomes applied for the antigen-presenting process.…”
Section: Exosomal Cargoes In Schistosomiasis Pathophysiologymentioning
confidence: 99%